Il chiostro di San Bartolomeo a Lipari: sperimentazioni progettuali e decorative nella prima comunità benedettina della Sicilia normanna - Tabanelli, Margherita (Hortus Artium Medievalium, 2017)
Abstract The most ancient Norman Benedictine abbey in Sicilian area is S. Bartolomeo in Lipari. Count Roger I and his brother Robert Guiscard established it a couple of years before the death of the latter in 1085. In 1767, an earthquake damaged the church, which was rebuilt as a three naves basilica. The current right aisle has replaced the northern side of the cloister. The cloister is probably the oldest one in Southern Italy. The quality of the capitals’ sculptures, as well as the lack of narrative scenes, attests that the cloister was built some decades after the abbey’s foundation, during the first half of the 12th century. The style of the sculptures has no comparisons in the Norman world, but it is possible to find similarities with the First-Romanesque production of Northern and Central Italy. The artists likely were part of the community of Lombard colonists invited in Sicily by count Roger and his wife Adelasia, as well as the first abbot, Ambrosius, and many monks. Both architecture and decoration of the monastic complex seem to have adapted themselves to the habits and the expectations of the first community of Lombard Benedictines, instead to them of their Norman patrons.